Analysis of Biophysical Potential and Urban Community Needs for Healing Forest in City Park 2 BSD, South Tangerang - Situmorang, Levana Kezia Natalia; Hermawan, Rachmad; Zuhud, Ervizal A.M. (Media Konservasi, 2026)
Healing forest attracts attention as one of the forms of preventive treatment that is affordable, safe, and free from side effects. City parks have great potential in supporting the well-being of urban communities. Based on SNI 9006:2021, City Park 2 BSD has characteristics that support its development as a healing forest, with several biophysical potentials that can be enhanced to create a more calming atmosphere. The biophysical potentials in City Park 2 BSD that require modification are temperature, humidity, and natural aromatherapy; therefore, it is necessary to plant more trees that can provide shade and improve air circulation, as well as select plant species that contain phytoncides. Urban communities have a high awareness of the importance of green open spaces that support mental and physical health. The community strongly supports all forms of development and facility renewal, with the main priorities being comfort, accessibility, basic facilities, and social interaction, such as meditation and yoga paths, relaxation rooms with natural sounds, aromatherapy gardens, color therapy gardens, and the provision of areas for picnics and family recreation. The collection of biophysical and social data is useful to identify gaps in the park so that management and development strategies can be proposed to transform City Park 2 BSD into a healing forest.